Health related quality of life in patients having schizophrenia negative symptoms – a systematic review - Chiraz Azaiez; Aurélie Millier; Christophe Lançon; Emilie Clay; Pascal Auquier; Pierre-Michel Llorca; Mondher Toumi (Journal of Market Access & Health Policy)
Background: Schizophrenia negative symptoms (SNS) contribute substantially to poor functional outcomes, loss in productivity and poor quality of life. It is unclear which instruments may be used for assessing quality of life in patients with SNS. Objective: The objective of this review was to identify instruments assessing health-related quality of life (HRQoL) validated in patients with SNS and to assess their level of validation. Data sources: We conducted a systematic literature review in Medline and the ISPOR database in March 2016 to identify studies on the quality of life in patients with SNS published by March 2016. Data extraction: Psychometric properties and validation steps. Data synthesis: After applying inclusion/exclusion criteria, 49 studies were selected for the analysis of HRQoL instruments; however, none of these instruments only addressed patients with SNS. Of these, 19 HRQoL instruments used in patients with schizophrenia or including patients with SNS among others, in the context of instrument validation, were identified (4 generic, 10 non-specific mental health, 5 schizophrenia-specific). Conclusion: No HRQoL instrument has been validated in patients with SNS only; for the remaining instruments identified, it remains unclear whether they were intended to capture HRQoL in patients with SNS.